Bahasa Inggris Bahasa Inggris - Henry Fairuz Widya Dhana; Rahmadi Rahmadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Even with the relentless introduction of digital marketing tools, e-commerce platforms are facing a noticeable plateau, evidenced by falling conversion rates and waning consumer enthusiasm. Lazada, a dominant market player, bets heavily on live streaming and flash sales to drive revenue, yet it remains unclear whether these high-level strategies actually resonate within specific local markets. Addressing this gap, this research explores the precise impact of these tactics on the purchasing behavior of Lazada users in Cirebon City. The study employs a quantitative methodology anchored in Partial Least Squares Structural Equation Modeling (PLS-SEM), drawing data from 120 local respondents who actively engage with these features. The results are decisive: live streaming significantly boosts sales, driven primarily by the immediacy of real-time interaction, the trustworthiness of the host, and the immersive quality of the broadcast. Flash sales also demonstrate clear effectiveness, successfully converting users by manufacturing urgency through time limits and scarcity. While both strategies combined account for a substantial portion of purchasing decisions, live streaming emerges as the superior influence in driving consumer action.